Covid 19 Pandemic, International Law and Women's Rights in Africa - Adeyoju Ilesanmi, Omotola (Universitas Medan Area, 2024)
The COVID-19 pandemic, which emerged in Wuhan, China, in late 2019, has been identified as one of the most severe forms of global public health crises that have confronted the world since World War I &II. Its rapid spread and debilitating impact made the world standstill as economies and health systems visibly shook. The Protocol to the African Charter on Human and People Rights on the Rights of Women in Africa and the Convention on the Eradication of All Forms of Discrimination Against Women CEDAW obligates states to ensure the protection of women's rights to respect for their dignity and protection from violence. However, measures instituted by domestic authorities to mitigate the spread of the COVID-19 disease, such as lockdowns, stay-at-home, and travel bans, have resulted in the infringement on such rights. Women's rights have been infringed on with increased violence against women, intimate partner violence, and gender-based violence. Similarly, access to healthcare services for women and girls was stifled, and their sexual and reproductive rights were primarily left to the sidelines with the diversion of resources to COVID-19 treatment, resulting in a significant increase in stillbirth, maternal depression, and maternal deaths. Using a desk review of secondary data, the paper interrogates the infringement of women's rights in Africa arising from the COVID-19 pandemic and the response and recovery measures instituted by African governments. The paper concludes that the response measures developed by states to combat the COVID-19 pandemic negatively impacted women's rights and gender equality in Africa. And that States failed in their obligations to promote and protect women's rights in Africa. It recommends that States and the African Union ensure the protection of women's rights in line with the goals of Agenda 2063.